Azimuthally Polarized, Circular Colloidal Quantum Dot Laser Beam Enabled by a Concentric Grating - Gao, Yuan (2017)
Since optical gain was observed from colloidal quantum dots (CQDs), research on CQD lasing has been focused on the CQDs themselves as gain materials and their coupling with optical resonators. Combining the advantages of a CQD gain medium and optical microcavity in a laser device is desirable. Here, we show concentric circular Bragg gratings intimately incorporating CdSe/CdZnS/ZnS gradient shell CQDs. Because of the strong circularly symmetric optical confinement in two dimensions, the output beam CQD-based circular grating distributed feedback laser is found to be highly spatially coherent and azimuthally polarized with a donut-like cross section. We also observe the strong modification of the photoluminescence spectrum by the grating structures, which is associated with modification of optical density of states. This effect confirmed the high quality of the resonator that we fabricated and the spectral overlap between the optical transitions of the emitter and resonance of the cavity. Single mode lasing has been achieved under a quasi-continuous pumping regime, while the position of the lasing mode can be conveniently tuned via adjusting the thickness of the CQD layer. Moreover, a unidirectional output beam can be observed as a bright circular spot on a screen without any collimation optics, presenting a direct proof of its high spatial coherence.